1995
DOI: 10.1063/1.360566
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the deep defect density in thin amorphous silicon films with the ‘‘absolute’’ constant photocurrent method

Abstract: Direct measurement of the deep defect density in thin amorphous silicon films with the help of the ‘‘absolute’’ constant photocurrent method is demonstrated here. We describe in detail how the optical (photocurrent) absorption spectrum can be measured directly in absolute units (cm−1) without additional calibration and undisturbed by interference fringes. Computer simulation was performed to demonstrate absolute precision of the measurement and to explain residual interferences which are sometimes observed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…The CPM setup described elsewhere 19 was used to measure the absorptance of the films both in the standard and absolute CPM mode. On top of the layers coplanar Al or Cr/Ag electrodes were evaporated with the interelectrode spacing D varying from 30 m to 3 mm and electrode width W between 2 and 8 mm ͑Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPM setup described elsewhere 19 was used to measure the absorptance of the films both in the standard and absolute CPM mode. On top of the layers coplanar Al or Cr/Ag electrodes were evaporated with the interelectrode spacing D varying from 30 m to 3 mm and electrode width W between 2 and 8 mm ͑Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the CPM method and evaluation are described elsewhere. 19 The most simple standard interpretation of the measured CPM spectra 20 uses the Beer's law expression for the absorptance of the film…”
Section: Aϭ1ϫrϫt ͑13͒mentioning
confidence: 99%
“…Presented formulae are for total absorptance, but characterizing light absorption by its total value is not always precise because absorption is generally not homogeneous due to many effects: 1) due to exponential decrease of intensity in absorbing material, 2) due to standing waves in thin films 3) due to inhomogeneity of material and thus inhomogeneity of absorption coefficient itself, 4) due to inhomogeneously distributed defects, for example close to surfaces of grain boundaries. Last two cases are not accounted in above presented calculations and so the measurement in A/T mode is not legitimate and has an effect of nonvanishing interference patterns (Vaněček et al 1995). Moreover this effect depends on position of highly absorbing sub-layer in the whole layer and if it is on the back side with respect to illumination, the non-vanishing interferences are not observed, inhomogeneity is masked but generally higher absorptance is observed, see Fig.…”
Section: From Defects To Absorption Coefficientmentioning
confidence: 99%
“…Mathematic fit of e.g. Cauchy formula parameters of refraction index or assumption of some typical spectrum of refraction index (Vaněček 1995) is possible for calculation of R 2 . The least sophisticated, but still used is to approximate the formula 11 into simple form 14 or 15.…”
Section: From Defects To Absorption Coefficientmentioning
confidence: 99%
“…However, both methods have limitations at lower energies to obtain reliable a(hm) values. Alternatively, photoconductivity techniques such as constant photocurrent method (CPM), both in standard [7] and absolute mode [8] and dual beam photoconductivity (DBP) [9] techniques have been used to derive absorption coefficients from the measured photoconductivity spectrum. No study has been reported for the direct calculation of absolute a(hm) spectrum using the DBP method yet.…”
Section: Introductionmentioning
confidence: 99%